Blog, social network e strategie narrative di resistenza nel post-terremoto dell’Aquila - Massimo Giuliani (Rivista di Psicologia dell'Emergenza e dell'Assistenza Umanitaria, 2013)
An earthquake, when it attacks a territory and its history, strikes the collective memory of a population. The reconstruction that followed the earthquake of L'Aquila contained elements that were equally problematic for the cohesion of the social and relational network, and therefore for mental health of stricken citizens and territories. Blogs, Facebook and online communication have been a possibility for the population (not only for the age group that usually makes use of digital technologies) to share informations, chronicles, narrations about the postearthquake and to tell a story that was different from the sweetened one told by media. While trying a way to process loss and their own discomfort, many authors and bloggers became datum points for a community of readers thanks to their stories and chronicles. In addition, for the active citizenry the virtual setting of the Web became a substitute to the physical agora that had been wiped out by the earthquake and the dispersion of the community all over national territory. The experience of L'Aquila, also recreated through conversations with bloggers and the observation of Facebook status updates, shows interesting elements in order to understand the role of new media in everyday life and in an exceptional context such as collective trauma